Analisis Pengelolaan Dana Bantuan Operasional Sekolah (BOS) Pada SMAN 1 SINGARAJA - Nyoman Trisna Kartini Putri; Anantawikrama Tungga Atmadja (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
The aim of this research is; To understand how the BOS fund management system at SMAN 1 Singaraja. To find out the application of the principle of accountability in the management of BOS funds at SMAN 1 Singaraja. The method used in this study is a qualitative research method, qualitative research in general can understand social phenomena from the point of view of the informant. Informants are people who are interviewed, observed, asked to provide data, opinions, thoughts, and perceptions in order to obtain relevant research results. The research data were obtained through in-depth interviews, observation and document studies. This data is then processed through three stages, namely data reduction, data presentation and data analysis and drawing conclusions based on predetermined theories. The results of this study indicate that the BOS fund reporting system at SMAN 1 Singaraja has been very clearly authorized, where each staff has the authority and responsibility in managing BOS funds and who has full power and responsibility here is the Principal as the head of the unit in the school.